Intravaginal rings as delivery systems for microbicides and multipurpose prevention technologies - Thurman AR; Clark MR; Hurlburt JA; Doncel GF (Dove Medical Press, 2013)
Andrea Ries Thurman, Meredith R Clark, Jennifer Hurlburt, Gustavo F Doncel CONRAD, Department of Obstetrics and Gynecology, Eastern Virginia Medical School, Norfolk, VA, USA Abstract: There is a renewed interest in delivering pharmaceutical products via intravaginal rings (IVRs). IVRs are flexible torus-shaped drug delivery systems that can be easily inserted and removed by the woman and that provide both sustained and controlled drug release, lasting for several weeks to several months. In terms of women's health care products, it has been established that IVRs effectively deliver contraceptive steroids and steroids for the treatment of postmenopausal vaginal atrophy. A novel application for IVRs is the delivery of antiretroviral drugs for the prevention of human immunodeficiency virus (HIV) genital infection. Microbicides are antiviral drugs delivered topically for HIV prevention. Recent reviews of microbicide IVRs have focused on technologies in development and optimizing ring design. IVRs have several advantages, including the ability to deliver sustained drug doses for long periods of time while bypassing first pass metabolism in the gut. IVRs are discreet, woman-controlled, and do not require a trained provider for placement or fitting. Previous data support that women and their male sexual partners find IVRs highly acceptable. Multipurpose prevention technology (MPT) products provide protection against unintended/mistimed pregnancy and reproductive tract infections, including HIV. Several MPT IVRs are currently in development. Early clinical testing of new microbicide and MPT IVRs will require a focus on safety, pharmacokinetics and pharmacodynamics. Specifically, IVRs will have to deliver tissue concentrations of drugs that are pharmacodynamically active, do not cause mucosal alterations or inflammation, and do not change the resident microbiota. The emergence of resistance to antiretrovirals will need to be investigated. IVRs should not disrupt intercourse or have high rates of expulsion. Herein, we reviewed the microbicide and MPT IVRs currently in development, with a focus on the clinical aspects of IVR assessment and the challenges facing microbicide and MPT IVR product development, clinical testing, and implementation. The information in this review was drawn from PubMed searches and a recent microbicide/MPT product development workshop organized by CONRAD. Keywords: contraception, HIV, microbicides